2002
DOI: 10.1007/bf03016873
|View full text |Cite
|
Sign up to set email alerts
|

Duration of control stimulation does not affect onset and offset of neuromuscular blockade at the corrugator supercilii muscle measured with phonomyography or acceleromyography

Abstract: P Pu ur rp po os se e: : Phonomyography (PMG) is a novel technique for measuring neuromuscular blockade (NMB). The effect of the duration of control stimulation on the onset and duration of blockade was investigated using PMG and acceleromyography (AMG).M Me et th ho od ds s: : After induction of anesthesia, a microphone was placed above the middle portion of the left eyebrow, and an acceleromyographic probe was placed above the middle portion of the right eyebrow. Twenty patients were randomized to receive bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…In our study, the multiple time points of muscle-relaxation recovery (T25%, T75%, and T90%) recorded via the PMG prototype and TOF-Watch SX were approximately similar. Lacking T90% data and differences in target muscle may be the contrast of results between our study and that of Hemmerling's [38]. Previous studies on the corrugator supercilii muscle offered an alternative choice for neuromuscular monitoring.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…In our study, the multiple time points of muscle-relaxation recovery (T25%, T75%, and T90%) recorded via the PMG prototype and TOF-Watch SX were approximately similar. Lacking T90% data and differences in target muscle may be the contrast of results between our study and that of Hemmerling's [38]. Previous studies on the corrugator supercilii muscle offered an alternative choice for neuromuscular monitoring.…”
Section: Discussioncontrasting
confidence: 80%
“…They found that the correlation coefficient of the T1 ratio between the two devices before and after the administration of a nondepolarizing neuromuscular blocker during induction of anesthesia was 0.906, suggesting that the PMG and the AMG were equally effective in determining the onset time of a nondepolarizing neuromuscular blocker. Hemmerling et al compared the neuromuscular-monitoring effect of PMG and AMG at the corrugator supercilii muscle in 20 patients undergoing general anesthesia, and they found that PMG recorded a longer onset time than that of AMG [38]. Our study focused on the adductor pollicis muscle and draws the result that the median onset time recorded via the PMG prototype was 74 s, while the median onset time recorded via TOF-Watch SX was 60 s. There was no significant difference in onset time between the two devices and the agreement was good.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The duration of control stimulation does not change the measured onset, maximum effect or offset of neuromuscular blockade. 11 The determination of the LOA between phonomyography and methods measuring the actual force of contraction has been very promising in showing narrow LOA. Our current research efforts deal with more technical questions as to whether the microphone size has an impact on sound detection and whether the size of the microphone influences measurement of neuromuscular blockade.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, they compared the pharmacodynamic data of mivacurium recorded by PMG-based and ACC-based equipment. However, the results implied that PMG was not interchangeable with ACC for measuring neuromuscular blockade at the corrugator supercilii muscle as PMG recorded a longer onset, a more pronounced maximal effect, and a faster recovery [ 23 ]. Second, given that the position of the microphone may influence the quality of sound signals, they processed another investigation to determine the best recording site for PMG at the corrugator supercilii muscle and concluded that the best recording site at this muscle for PMG is located between the anterior midline and the lateral part of the forehead, over the eyebrow.…”
Section: The Development Of Pmg-based Equipment For Perioperative Neu...mentioning
confidence: 99%